PENGEMBANGAN BAHAN AJAR PEMBELAJARAN PJOK MATERI LEMPAR BERBASIS MULTIMEDIA INTERAKTIF ARTICULATE STORYLINE PADA SISWA KELAS VII - Firdaus, Muhammad Anwar; Nurrochmah, Siti; Supriyadi, Supriyadi (Gelanggang Pendidikan Jasmani Indonesia, 2024)
The purpose of writing this development research is to develop PJOK teaching materials, interactive multimedia-based throwing material, articulate storyline for class VII students at MTs Negeri Tulungagung, presenting clarity, interest, convenience and usefulness of content as a medium for learning throwing movements which previously was done only when children wanted to move with limited study hours. limited. The "ADDIE" development research model uses five stages, analyzing, designing, developing, implementing and evaluating the results of the products that have been created. The research subjects for class VII students at MTs Negeri Tulungagung consisted of 15 students for small group trials, 180 for large group trials. Using questionnaires or questionnaires as instruments. The data analysis technique uses descriptive statistics with a quantitative descriptive approach. From the results of the trials that have been carried out, the accumulated percentage of the small group is 87% and the large group is 89% with a very feasible category. The conclusion obtained is that interactive multimedia throwing teaching materials for class VII students at MTs Negeri Tulungagung are suitable for use in the PJOK learning process.